Human rights, democracy and embargo: Rafael Correa's vision of political relations between the United States and Cuba - Barrera Rivera, Dan Abner (2020)
The purpose of this article is to analyze the role played by Rafael Correa in the political relations between the governments of the United States and Cuba.  The former Ecuadorian president addresses the issues of human rights and democracy in the context of the Cuban Embargo that has endured for almost six decades.  The present research was carried out by studying ten videos in which Correa dwells on these subjects; seven videos were interviews and the other three conferences.  Considering the main subject axes (human rights, democracy and embargo) we proceeded to compare the allocutions, relate similarities and deepen the ideas; next, in-depth hermeneutics of the text (videos) were made within the context of the interview itself (sometimes controversial and other times more fraternal); finally, the exhibitor's thinking was systematized following the chronological order of his presentations.  Bibliographic sources (historical, biographical and philosophical), from authorized writers, were also used to sustain some of the developed ideas.  Some of the conclusions are: it is impossible to seriously analyze the Cuban political system without accounting for the economic, commercial and financial embargo suffered by the Island; Cuba possesses a socialist political system wherein a participatory democracy has developed; the embargo is effectively one of the greatest human rights violations of an entire nation; and, the opposition and rejection of the embargo stems from a matter of respect for international law and not due to political sympathies with the Cuban government.  This article merely constitutes an exploratory approach on the subject matter and invites to deeper inquire.